The Angiosperm Stem Hemiparasitic Genus Cassytha (Lauraceae) and Its Host Interactions: A Review - Hongxiang Zhang; Hongxiang Zhang; Singarayer Florentine; Kushan U. Tennakoon (Frontiers in Plant Science, 2022)
Cassytha, also known as laurel dodder or love vine, is a stem hemiparasite of the Lauraceae family. It has long been used for medicinal purposes in many countries and has increasingly influenced agricultural and natural ecosystems by its effects on a wide range of host species. Previous studies have focused on the taxonomy and evolutionary position of different Cassytha, with the pan-tropical species Cassytha filiformis being the most widely studied. However, Cassytha–host interactions have never been reviewed, which is an essential issue related to the understanding of mechanisms underlying plant hemiparasitic and the assessment of benefits and damage caused by aerial parasitic plants. This review explores the parasitic habits, worldwide distribution, and host range of Cassytha, and examines its impacts on the biology of host plants and the overall influence of environmental changes on Cassytha–host associations. We also comment on areas of future research directions that require to better understanding Cassytha–host interactions. It appeared that some traits, such as flowering phenology, facilitated Cassytha’s widespread distribution and successful parasitism and that Cassytha preferred woody species rather than herbaceous species as a host, and preferred species from certain families as hosts, such as Fabaceae and Myrtaceae. Cassytha often decreased biomass and impacted the physiology of host species and global environmental changes seemed to intensify the negative impacts of Cassytha on their hosts. Cassytha was not only a noxious weed, but can also function as a biocontrol agent to mitigate alien plant invasion.